Class 10 Math All topics Quadratic Equations

Simplify $x−aa +x−bb =x−c2c $

Solution:

$x−aa +x−bb =x−c2c $

$⇒(x−a)(x−b)a(x−b)+b(x−a) =(x−c)2c $

$⇒(ax−ab+xb−ab)(x−c)=2c(x_{2}−ax−bx+ab)$

$⇒[(a+b)x−2ab](x−c)=2cx_{2}−2acx−2bcx+2abx.$

Similar topics

introduction to trigonometry

functions

some applications of trigonometry

quadratic equations

polynomials

introduction to trigonometry

functions

some applications of trigonometry

quadratic equations

polynomials

Related Questions

Related Questions